2014
DOI: 10.5130/ajceb.v14i1.3745
|View full text |Cite
|
Sign up to set email alerts
|

Managing geotechnical risk on US design-build transport projects

Abstract: Awarding design-build (DB) contracts before a complete subsurface investigation is completed, makes mitigating the risk of differing site conditions difficult, if not impossible. The purpose of the study was to identify effective practices for managing geotechnical risk in DB projects, and it reports the results of a survey that included responses from 42 of 50 US state departments of transportation and a content analysis of DB requests for proposals from 26 states to gauge the client's perspective, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It is conceivable but not obvious that the use of performance specifications may be affected if the choice of a design-build contract is influenced by a wish to accelerate projects, an intention that appears to be more common in the US than for Swedish public clients. If as a consequence the time allotted to geotechnical investigations is shorter than under designbid-build, contractors are exposed to additional risk (McLain, Gransberg and Loulakis, 2014;Castro-Nova et al, 2018).…”
Section: Hierarchies Of Performance Requirementsmentioning
confidence: 99%
“…It is conceivable but not obvious that the use of performance specifications may be affected if the choice of a design-build contract is influenced by a wish to accelerate projects, an intention that appears to be more common in the US than for Swedish public clients. If as a consequence the time allotted to geotechnical investigations is shorter than under designbid-build, contractors are exposed to additional risk (McLain, Gransberg and Loulakis, 2014;Castro-Nova et al, 2018).…”
Section: Hierarchies Of Performance Requirementsmentioning
confidence: 99%
“…In addition, the amount of geotechnical information expressed in the procurement phase plays an important role in the probability that a given DB project will end in a DSC claim. McLain et al found that providing all the geotechnical information on hand when the project is advertised and forming the DSC clause in a manner that makes it specific to the available geotechnical data instead of using a standard design-bid-build boilerplate DSC was an effective alternative to manage geotechnical risk (14).…”
Section: Introductionmentioning
confidence: 99%
“…Daoulas addresses key elements that should be considered regarding geotechnical risk during the proposal preparation phase (13). Another study suggests that effective practices, such as enhancing communication between the owner and the design-builder, using differing site condition clauses, and expediting geotechnical design reviews after the contract is awarded, can be employed to mitigate or reduce the geotechnical risk (14). Likewise, other studies have concentrated specifically on the legal aspects of DB geotechnical issues (15).…”
mentioning
confidence: 99%
“…In addition, the amount of geotechnical information expressed in the procurement phase plays an important role over the probability to a given DB project ends in a DSC claim. McLain et al (2014) found that providing all the geotechnical information on hand when the project is advertised and forming the DSC clause in a manner that makes it specific to the available geotechnical data instead of using a standard DBB boilerplate DSC was an effective alternative to manage geotechnical risk.…”
Section: Introductionmentioning
confidence: 99%